Anti-inflammatory Effects of Channa micropeltes Extract through NF-κB and TNF-α in Diabetic Rat - Carabelly, Amy Nindia; Aspriyanto, Didit; Sari, Milka Widya; Norfitriyah, Erika; Utami, Juliyatin Putri (Majalah Obat Tradisional, 2024)
Diabetes mellitus (DM) is a disorder of carbohydrate, fat, and protein metabolism caused by impaired insulin secretion, insulin action, or both characterized by hyperglycemia. Hyperglycemic condition is associated with inflammation process leading to complications. Food supplements play an important role in controlling protein metabolism and have anti-inflammatory properties such as Channa micropeltes (CM). This study aimed to analyze the effect of CM extract on the levels of molecular markers Nuclear factor kappa beta (NF-κB) and Tumor Necrosis Factor alfa (TNF-α) in normal and diabetic rats. The experimental design of this investigation was a post-test-only control group design and the samples were the diabetic model group given CM extract at 16 mL/kgBB dose, and negative control group for 14 days, respectively. Serum concentrations of    NF-κB and TNF-α were measured by ELISA. DM-CM group showed decreasing levels of NF-κB. TNF- α was detected with the lowest level in the N-CM group. The levels of TNF- α declined close to normal levels in the DM-CM group. Hence, the conclusion was the CM at a dose of 16 mL/kg BW for 14 days in Wistar rats can reduce Nf-κB and TNF-α in groups of normal and diabetic rats.